Adaptability of the gut microbiota of the German cockroach Blattella germanica to a periodic antibiotic treatment - Marín-Miret, Jesús; Pérez-Cobas, Ana Elena; Domínguez-Santos, Rebeca; Pérez-Rocher, Benjamí; Latorre, Amparo; Moya, Andrés (Microbiological research, 2024)
High-throughput sequencing studies have shown that diet or antimicrobial treatments impact animal gut microbiota equilibrium. However, properties related to the gut microbial ecosystem stability, such as resilience, resistance, or functional redundancy, must be better understood. To shed light on these ecological processes, we combined advanced statistical methods with 16 S rRNA gene sequencing, functional prediction, and fitness analyses in the gut microbiota of the cockroach Blattella germanica subject to three periodic pulses of the antibiotic (AB) kanamycin (n=512). We first confirmed that AB did not significantly affect cockroaches' biological fitness, and gut microbiota changes were not caused by insect physiology alterations. The sex variable was examined for the first time in this species, and no statistical differences in the gut microbiota diversity or composition were found. The comparison of the gut microbiota dynamics in control and treated populations revealed that (1) AB treatment decreases diversity and completely disrupts the co-occurrence networks between bacteria, significantly altering the gut community structure. (2) Although AB also affected the genetic composition, functional redundancy would explain a smaller effect on the functional potential than on the taxonomic composition. (3) As predicted by Taylor's law, AB generally affected the most abundant taxa to a lesser extent than the less abundant taxa. (4) Taxa follow different trends in response to ABs, highlighting "resistant taxa," which could be critical for community restoration. (5) The gut microbiota recovered faster after the three AB pulses, suggesting that gut microbiota adapts to repeated treatments. •Antibiotics do not directly affect B. germanica physiology.•Males and females of B. germanica have similar gut microbial communities.•Antibiotics disturb the network of interactions in the cockroach gut microbiome.•Gut functional redundancy buffers the effect of antibiotics.•Gut microbiota adapts to repeated antibiotic treatments.